Proses Perlindungan Hukum terhadap Korban Kekerasan dalam Rumah Tangga Berdasarkan Undang – Undang N0 23 Tahun 2004 - Muhammad Fauzitri Hanggara; Tri Reni Novita (Jurnal Smart Hukum (JSH), 2023)
Birth of Law No. 23 of 2004 concerning the Elimination of Domestic Violence brings a bright spot for women who are vulnerable to becoming victims of acts of Domestic Violence. The problem of Domestic Violence (KDRT) is no longer a private problem but a public problem. The absence of laws protecting victims of violence can no longer be used as an excuse for the high number of cases of violence against women. Even the birth of this law regulates specifically the cooperation of several parties to provide legal protection/victims. Protection of victims also means protection of human rights. Domestic Violence is also an act that violates Human Rights. Victims of Domestic Violence need protection and assistance. Apart from the state, one of the parties that can provide protection for victims of domestic violence is a social institution whose struggle is specifically for women. In the Government's efforts to provide legal protection and the role of social institutions in providing legal protection, the factors that play a role in providing legal protection are the main issues discussed in this thesis. Domestic Violence is an act that can traumatize the victim as well as physical violence. Therefore in Law no. 23 of 2004 is expected to be a tool that can stop the culture of violence that exists in society. Women as the first and foremost educators in a family, for this reason, are expected to be able to develop values of compassion, equality and equality, caring for one another. The conclusion of this study is that there have been too many incidents of Domestic Violence, for this reason Law No. 23 of 2004 concerning Domestic Violence was made. In the contents of Article 4 Paragraph (1) of the Law on the Elimination of Domestic Violence Any person who commits acts of physical violence in the household as referred to in Article 5 letter a shall be subject to imprisonment for five years or a fine of up to Rp. 15,000,000